2002
DOI: 10.1161/hh0402.105791
|View full text |Cite
|
Sign up to set email alerts
|

Retrovirally Mediated Overexpression of Versican V3 by Arterial Smooth Muscle Cells Induces Tropoelastin Synthesis and Elastic Fiber Formation In Vitro and In Neointima After Vascular Injury

Abstract: Abstract-Versican is an extracellular matrix (ECM) proteoglycan that is synthesized as multiple splice variants. In a recent study, we demonstrated that retroviral-mediated overexpression of the variant V3, which lacks chondroitin sulfate (CS) chains, altered arterial smooth muscle cell (ASMC) phenotype in short-term cell culture. We now report that V3-overexpressing ASMCs exhibit significantly increased expression of tropoelastin and increased formation of elastic fibers in long-term cell cultures. In additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
100
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 89 publications
(111 citation statements)
references
References 32 publications
11
100
0
Order By: Relevance
“…Elastic fiber deposition was examined by immunofluorescence using anti-tropoelastin antibodies after 3 weeks of culture. Consistent with our previous studies (19,28), V3 expression by ASMCs significantly increased mRNA levels of tropoelastin as well as fibulin 5, a component of microfibrils critical in elastic fiber formation (Fig. 1, A and B) (22)(23)(24).…”
Section: V3 Expression Enhances Elastic Fiber Formation and Mrna Exprsupporting
confidence: 92%
See 2 more Smart Citations
“…Elastic fiber deposition was examined by immunofluorescence using anti-tropoelastin antibodies after 3 weeks of culture. Consistent with our previous studies (19,28), V3 expression by ASMCs significantly increased mRNA levels of tropoelastin as well as fibulin 5, a component of microfibrils critical in elastic fiber formation (Fig. 1, A and B) (22)(23)(24).…”
Section: V3 Expression Enhances Elastic Fiber Formation and Mrna Exprsupporting
confidence: 92%
“…Deficiency in fibulin 2 and fibulin 5 in animals results in disrupted elastic laminae accompanied by an increase in vascular adhesion molecules and tissue factor expression as well as thrombus formation after carotid artery ligation injury (23), suggesting that the elastin-enriched ECM present in healthy aortas protects against vascular injury. Previously, we have demonstrated that expression of the V3 isoform of versican in ASMCs generates an ECM enriched in elastic fibers and that this ECM had reduced capacity to bind monocytes (4,18,19,28). We now show a causal relationship between changes in elastin accumulation and monocyte adhesion such that knocking down tropoelastin or fibulin 5, a component of microfibrils critical for elastic fiber formation (22)(23)(24), partially reverses the inhibition of monocyte adhesion caused by V3 expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The repair of damaged elastic fibres within these tissues remains a difficult challenge for biomedicine, but in tissues such as photoaged skin, topical treatment with all-trans retinoic acid has been shown to promote the deposition of fibrillin-1 but not of type I collagen (Watson et al 2008). In the vasculature, whilst there is a great deal of interest in the potential of in vitro tissue engineering approaches (for a review see Kielty et al 2007), Merrilees and coworkers have demonstrated the ability of an ECM glycoprotein (verscian) to stimulate elastic fibre deposition in vivo (Merrilees et al 2002). Perhaps the best hope, however, lies with preventing the damage from occurring; elastic fibres have a widespread tissue distribution, where they fulfil vital mechanical and biochemical roles and are uniquely long-lived and hence susceptible the accumulation of age-related damage.…”
Section: Conclusion: Repairing and Preventing Elastic Fibre Degradationmentioning
confidence: 99%
“…Elastic fiber formation may also be regulated by the pericellular matrix. For example, retrovirally mediated overexpression of versican splice variant V3 by arterial smooth muscle cells induced tropoelastin synthesis and elastic fiber formation in vitro and in neointima after vascular injury [53]. This was proposed to be due to removal of the chondroitin sulfate containing forms of versican, VO and V1, by competition for hyaluronan in the pericellular matrix.…”
Section: Role Of the Pericellular Matrix In Ecm Assemblymentioning
confidence: 99%